Changes in plant community structure and decrease in floral resource availability lead to a high temporal β-diversity of plant–bee interactions - Hachuy-Filho, Leandro [UNESP]; Ballarin, Caio S. [UNESP]; Amorim, Felipe W. [UNESP] (Springer Nature, 2020)
Biological communities are subject to spatiotemporal variations in community structure, i.e., species composition, richness, and abundance. Plant–pollinator interactions are affected by species composition and abundance, so that rapid changes in plant community structure can lead to critical impacts on plant–pollinator interactions at the community level. The extent of these impacts depends on how plants respond to different kinds of stressors, such as the disturbance caused by invading species. In this research, we conducted a before-and-after study to evaluate the potential effects of an invasive fast-growing alien grass species on the structure of a plant–pollinator interaction network. We described the changes in community structure and plant–pollinator interactions over two sampling periods, through the temporal β-diversity of plant and bee species, plant–bee interactions, and plant functional traits. Our results showed that changes in plant community composition (especially the plants in the network core) and decrease in plant species richness, as well as in floral resources availability impacted plant–pollinator interactions of a grassland community after the growth of a fast-growing alien grass species. These changes were accompanied by a decrease in plant–bee interaction diversity, and a high β-diversity of species interactions mainly due to interaction rewiring. However, we found no effect on the functional diversity of flowers. In conclusion, our study showed that a short-term change in plant species composition and floral resource abundance impacted plant–bee interactions, which markedly changed network structure and dynamics.
Keywords: Functional diversity; Interaction turnover; Invasive species; Pollination network; β-diversity